Distributed Parameter Bioprocess Plant Identification and I-Term Control Using Decentralized Fuzzy-Neural Multi-Models - Baruch, Ieroham; Galvan-Guerra, Rosalba; M., Sergio-Miguel Hernandez (IntechOpen, 2011)
None